The Wedding Feast of Caranus the Macedonian by Hippolochus - Dalby, Andrew (Petits Propos Culinaires, 1988)
Andrew Dalby, who furnished a new translation of The Banquet by Philoxenus in PPC 26, here performs the same service for another important text. Like the piece by Philoxenus, that by Hippolochus survives only in the pages of The Deipnosophists by Athenaeus. Dating back to the 3rd century BC, it seems to be the earliest surviving text which is devoted exclusively to the description of a banquet; and it has many other features of interest. This is the first article to be written about it, and the first time when it has been presented on its own.